2012
DOI: 10.1371/journal.pone.0036987
|View full text |Cite
|
Sign up to set email alerts
|

Edwardsiella Comparative Phylogenomics Reveal the New Intra/Inter-Species Taxonomic Relationships, Virulence Evolution and Niche Adaptation Mechanisms

Abstract: Edwardsiella bacteria are leading fish pathogens causing huge losses to aquaculture industries worldwide. E. tarda is a broad-host range pathogen that infects more than 20 species of fish and other animals including humans while E. ictaluri is host-adapted to channel catfish causing enteric septicemia of catfish (ESC). Thus, these two species consist of a useful comparative system for studying the intricacies of pathogen evolution. Here we present for the first time the phylogenomic comparisons of 8 genomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 63 publications
9
107
1
Order By: Relevance
“…SPI1 is required for invasion into epithelial cells, while intracellular accumulation of Salmonella in macrophages is dependent on SPI2 function (Hansen-Wester & Hen sel 2001). In contrast, a whole-genome comparison of multiple E. tarda strains revealed that E. tarda genotypes were broadly clustered into 2 major subpopulations: pathogenic E. tarda genotype EdwGI, which represents a genotype of fish pathogens and possesses virulence factor genes such as T3SS and the Type VI secretion system (T6SS); and the nonpathogenic or environmental E. tarda genotype EdwGII (Yang et al 2012). Further, E. tarda isolated from red sea bream had T3SS (Et-LEE) and T6SS (Et-T6SS2) genes, which suggests that the genotype EdwGI could be divided into 2 sub-genotypes, viz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPI1 is required for invasion into epithelial cells, while intracellular accumulation of Salmonella in macrophages is dependent on SPI2 function (Hansen-Wester & Hen sel 2001). In contrast, a whole-genome comparison of multiple E. tarda strains revealed that E. tarda genotypes were broadly clustered into 2 major subpopulations: pathogenic E. tarda genotype EdwGI, which represents a genotype of fish pathogens and possesses virulence factor genes such as T3SS and the Type VI secretion system (T6SS); and the nonpathogenic or environmental E. tarda genotype EdwGII (Yang et al 2012). Further, E. tarda isolated from red sea bream had T3SS (Et-LEE) and T6SS (Et-T6SS2) genes, which suggests that the genotype EdwGI could be divided into 2 sub-genotypes, viz.…”
Section: Discussionmentioning
confidence: 99%
“…Edwardsiella tarda Type III secretion system (T3SS) gene cluster and location of insertional mutations. E. tarda T3SS is composed of 35 genes encoding apparatuses, translocons, effectors, regulators, chaperones, and known-function and hypothetical proteins (Tan et al 2005, Yang et al 2012. The chloramphicol resistance (Cm r ) gene was inserted in the possible effector and hypothetical genes by an allelic exchange method using the suicide vector pRE112 homo logy both to the spiC effector gene and the ssaB T3SS apparatus gene of S. enterica.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In the T3SS gene cluster, the concomitant 2-component system (TCS) EsrA-EsrB is essential for the bacterium's pathogenesis. 6,31 To better decipher the regulatory roles and the regulatory mechanisms of the response regulator EsrB, we performed RNA-seq analysis with EIB202 and DesrB RNA isolated from LB (n D 3) and DMEM cultures (n D 3) and compared their differential gene expression. DMEM was used to induce the expression of T3SS and T6SS proteins possibly by mimicry of in vivo or intracellular condition.…”
Section: Rna-seq Profiling Of the E Piscicida Transcriptomementioning
confidence: 99%
“…3 Elucidating the genes controlled by TCS will facilitate the understanding of the mechanisms underlying TCS scouting of environmental/host cues and switching gene expression and ultimately lead to the development of antibacterial therapies. 4 Edwardsiella piscicida (formerly included in E. tarda), 5,6,7,8 a member of the Enterobacteriaceae, colonizes a broad range of hosts including fish and mammals and causes fatal hemorrhagic septicemia and gastro-and extra-intestinal infections. 9,10,11,12 As a leading pathogen that threats fresh and seawater aquaculture farms, E. piscicida causes huge economic losses to the world aquaculture industry, especially for farmed flatfish (turbot and flounder).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation